Peran Mahkamah Konstitusi Dalam Penegakan Hukum Konstitusi - Maruarar Siahaan (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The enforcement of constitutional law as stated in the authority of the Indonesian Constitutional Court may will run effectively in the form of equal horizontal-functional based on the doctrine of checks and balances in the separation of power, when the verdict issued by this constitutional court is accepted and implemented by the concerned parties. The Indonesian Constitutional Court may safeguard their verdicts in the form of Conditional Constitutionality and Grace Period in order to implement the verdict which states whether an act in unconstitutional, however this cannot guarantee that the constitutional law will run. All related aspects are actually subject to the political-will of the government (executives) and legislators (law makers).Keywords: the constitution court, law enforcement